2020
DOI: 10.3758/s13415-020-00796-3
|View full text |Cite
|
Sign up to set email alerts
|

Mistakes that matter: An event-related potential study on obsessive-compulsive symptoms and social performance monitoring in different responsibility contexts

Abstract: Mistakes that affect others often are linked to increased feelings of responsibility and guilt. This especially holds for individuals high in obsessive-compulsive symptoms (OCS), who are characterized by inflated feelings of responsibility and a fear of causing harm to others. This event-related potential study investigated individual differences in OCS in social performance monitoring with a focus on the role of responsibility for other's harm and the error-related negativity (ERN). Healthy volunteers low (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Larger ERN amplitudes in OCD appear to be unrelated to performance or adjustment of behavior within-task, such as post-error slowing. This could suggest deficient translation of monitoring signals into adaptive behavior and therefore a failure to implement control (Endrass et al, 2010 ; Jansen and de Bruijn, 2020 ). Another explanation, which might fit with clinical representations of OCD, might be misguided self-control: such that in OCD self-control is applied in an inadequate or counterproductive manner (such as washing hands 50 times a day to prevent infection transforms a usually adaptive behavior—hand washing—into a self-control problem, presenting as excessive behavior) (Heatherton and Wagner, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Larger ERN amplitudes in OCD appear to be unrelated to performance or adjustment of behavior within-task, such as post-error slowing. This could suggest deficient translation of monitoring signals into adaptive behavior and therefore a failure to implement control (Endrass et al, 2010 ; Jansen and de Bruijn, 2020 ). Another explanation, which might fit with clinical representations of OCD, might be misguided self-control: such that in OCD self-control is applied in an inadequate or counterproductive manner (such as washing hands 50 times a day to prevent infection transforms a usually adaptive behavior—hand washing—into a self-control problem, presenting as excessive behavior) (Heatherton and Wagner, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activity in pMFC and AI is enhanced when errors result in painful versus non-painful outcomes for a friend (Koban et al 2013 ) and when participants are fully responsible for painful outcomes compared to when they share responsibility for errors with another recipient (Cui et al 2015 ). Recent studies from our lab indicate increased ERNs when errors have negative consequences for others (de Bruijn et al 2020 ) and suggest that the extent to which the social context affects performance-monitoring activity depends on individual differences such as psychopathic- (Overgaauw et al 2020 ) and obsessive–compulsive traits (Jansen & de Bruijn 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Functional magnetic resonance imaging (fMRI) studies have highlighted that performance-monitoring processes involve several emotional and cognitive brain regions. While correct responses and positive outcomes have been associated with ventral striatum (VS) activity, erroneous responses and negative performance feedback typically activate the posterior medial frontal cortex (pMFC) and the anterior insula (AI) (de Bruijn et al 2009 ; Koban et al 2013 ; Krönke et al 2018 ; Overgaauw, Jansen, & de Bruijn 2020 ; Radke et al 2011a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, OCD's electrophysiological characterization appears less univocal (84,85). Several studies reported abnormalities in event-related brain activity at various latencies (86)(87)(88). The power spectrum of spontaneous brain activity in OCD was also found to significantly differ from the one associated with healthy brain activity (89-98), the general finding being an increase in delta and theta band power (2-6 Hz) and a decrease in the alpha band (8-10 Hz) (99).…”
Section: Introductionmentioning
confidence: 99%